Food and Diaspora: An Exploration in M.G. Vassanji’s the Book of Secrets (British Journal of Multidisciplinary and Advanced Studies, 2025)
M.G. Vassanji’s The Book of Secrets intricately examines themes of displacement, cultural memory, and adaptation within the diasporic experience. Food emerges as a significant motif, representing both the preservation and transformation of identity in a foreign land. Through the novel’s exploration of East African Indian communities, Vassanji highlights the ways in which culinary traditions serve as repositories of memory and mediums for intergenerational knowledge transmission. This paper investigates the role of food in The Book of Secrets as a symbol of cultural continuity and change, focusing on its function in sustaining identity, negotiating hybridity, and reinforcing familial and communal bonds. Drawing on theoretical insights from postcolonial studies, including the works of Homi Bhabha, Stuart Hall, and Gayatri Chakravorty Spivak, the study argues that food encapsulates the complex realities of diasporic existence. The paper concludes that the novel’s depiction of food is central to understanding the emotional and cultural dimensions of displacement, as culinary practices become sites of both resistance and transformation.